Effect of copper nanoparticles exposure in the physiology of the common carp (Cyprinus carpio): Biochemical, histological and proteomic approaches - Yugantak Raj Gupta; Durai Sellegounder; Monica Kannan; Seetharam Deepa; Balasubramanian Senthilkumaran; Yaraguntappa Basavaraju (Aquaculture and Fisheries, 2016)
Copper nanoparticles (Cu-NPs) are serious water pollutants but their impact in teleosts performance remains poorly understood. In the present study, we have exposed juvenile carps (Cyprinus carpio), a freshwater teleost edible in India to two different doses (20 and 100 μg/L) of Cu-NPs for seven days. The doses selected were eco-relevant considering the contamination levels of certain water resources. The results indicated that the activity oxidative stress enzymes catalase, superoxide dismutase, and glutathione-S-transferase were significantly increased in the kidney, liver and gills of the treated groups when compared to control. Histological analysis revealed that after exposure, disruption of the secondary lamellae of gills, liver damage with pyknotic nuclei and structural disarray of the kidney occurred. Proteomic analysis of the liver showed down-regulation of several proteins including the ferritin heavy chain, rho guanine nucleotide exchange factor 17-like, cytoglobin-1 and up-regulation of diphosphomevalonate decarboxylase and selenide & water dikinase-1. Taken together, the results of suggest that short-term exposure of juvenile carp to Cu-NPs causes oxidative stress and impart serious deleterious effects in the tissues which may affect fish growth and development.